Drought Monitoring and Analysis over Haihe River Basin Based on GRACE and MODIS Datasets - DU Yichen; CHEN Jiangzhaoxia; ZHANG Yuqi; SUN Ruiqi; YANG Haibo (Renmin Zhujiang)
The Haihe River Basin is one of the most important watersheds in China,and its drought situations affect the industrial and agricultural production andpeople's lives in the region. This paper analyzes the spatial and temporalevolution characteristics of groundwater and surface vegetation coverage in theHaihe River Basin with the GRACE (Gravity Recovery and Climate Experiment) data,MODIS data, precipitation and evaporation data of 23 sites from 2003 to 2015,and builds a drought comprehensive index evaluation model by TOPSIS (Technique forOrder Preference by Similarity to Ideal Solution) method to reflect the droughtdynamics. The results show that: The water height of the Haihe River Basinindicates a significant annual change with a general downward trend; NDVI(Normalized Difference Vegetation Index) shows a strong seasonal correlation inthe time series, and shows a northwest-southeast band distribution in the spatialseries; There was a slight drought in the Haihe River basin between 2003 and2015, of which 2014 was the most severe; In terms of spatial distribution, thedrought mainly occurs in the Daqing River and the northern part of Yongding Riverin summer, while in Luanhe River and Zhangwei River in spring and autumn. Throughcomparison with the SPEI (Standardized Precipitation Evapotranspiration Index), itis verified that the drought comprehensive index model has good availability. Theresearch can provide a valuable reference for water resources drought monitoringin the Haihe River Basin.